Dwa nazwiska i jeden przydomek z Warmińskiej sagi […] Edwarda Cyfusa - Szcześniak, Krystyna (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2020)
The article explains the etymology of two surnames (Cyfus, Stynka / Stinka) and one nickname replacing a surname very popular in the region (Karaśniki). All anthroponyms occur in Edward Cyfus Warmian saga, which is popular not only in the region. A few recipes based on stynka and karaś, fish widely used in the region of Warmia and Mazury before WWII are attached to the text due to the reason explained in the article.